The effects of TNF alpha inhibition on plasma fibrinolytic balance in patients with chronic inflammatory rheumatical disorders - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2006)
Objectives. Recent studies support an inflammatory basis for atherosclerosis. Patients with chronic inflammatory rheumatical disorders are at increased risk for cardiovascular events, and this can be partially attributed to the inhibition of fibrinolytic system. TNF alpha inhibitors such as.infliximab are shown to retard the progression of inflammatory arthritides. In this study, we investigated the effects of infliximab on plasma fibrinolytic parameters. Methods. Thirteen patients (7 female, 6 male; mean age: 44 +/- 11 years) with a clinical indication for infliximab (rheumatoid arthritis (RA) (n = 8), ankylosing spondylitis (AS) (n = 5)) were selected. Plasma plasminogen activator inhibitor (PAI-1), tissue plasminogen activator (t-PA) antigens (Ag) and high sensitive C-reactive protein (hs-CRP) levels were measured during low salt intake at baseline. All patients received infliximab (Remicaide (R), i.v. infusion, 3 mg/kg). Plasma PAI-1 Ag, tPA Ag and hs-CRP were measured during low salt intake at the end of 2 weeks. All samples were collected at 9 AM. Antigen levels were determined using a 2-site enzyme-linked immuno-sorbent assay. Results. Patients experienced significant improvement in disease related activity scores after infliximab treatment. DAS score (for rheumatoid arthritis) and BASDAI index (for ankylosing spondylitis) decreased significantly after treatment (p = 0.01 and p = 0.04 respectively). Infliximab significantly reduced the marker of. inflammation (hs-CRP) (8.3 +/- 3.9 vs. 4 +/- 4.1 mg/L, p < 0.01). Plasma PAI-1 antigen (64.7 +/- 26.9 vs. 40 +/- 31.1 ng/ml, p = 0.03) and PAI-1/t-PA ratio (10.8 +/- 5.9 vs. 6.6 +/- 3.8, p = 0.02) were significantly lower after the treatment. In contrast, plasma t-PA levels were unchanged (9.4 +/- 4.4 vs. 9.0 +/- 4.3 ng/ml, p = 0. 73). Conclusion. This study provides evidence that TNF alpha inhibition with infliximab decreases PAI-1 Ag level and PAI-1/t-PA ratio, and hence activates fibrinolytic system in patients with chronic inflammatory disorders.
Keywords: TNF alpha inhibition; plasma fibrinolytic balance; PAI-1; t-PA; NECROSIS-FACTOR-ALPHA; PLASMINOGEN-ACTIVATOR INHIBITOR-1; CORONARY-HEART-DISEASE; ENDOTHELIAL-CELLS; MONOCLONAL-ANTIBODY; ARTHRITIS PATIENTS; RAPID INHIBITOR; INFLIXIMAB; ATHEROSCLEROSIS; METHOTREXATE